Diffusion tensor imaging and MR morphometry of the central auditory pathway and auditory cortex in aging - Profant, O; Škoch, A; Balogová, Z; Tintěra, J; Hlinka, J; Syka, J (Neuroscience, 2014)
Age-related hearing loss (presbycusis) is caused mainly by the hypofunction of the inner ear, but recent findings point also toward a central component of presbycusis. We used MR morphometry and diffusion tensor imaging (DTI) with a 3T MR system with the aim to study the state of the central auditory system in a group of elderly subjects (>65years) with mild presbycusis, in a group of elderly subjects with expressed presbycusis and in young controls. Cortical reconstruction, volumetric segmentation and auditory pathway tractography were performed. Three parameters were evaluated by morphometry: the volume of the gray matter, the surface area of the gyrus and the thickness of the cortex. In all experimental groups the surface area and gray matter volume were larger on the left side in Heschl's gyrus and planum temporale and slightly larger in the gyrus frontalis superior, whereas they were larger on the right side in the primary visual cortex. Almost all of the measured parameters were significantly smaller in the elderly subjects in Heschl's gyrus, planum temporale and gyrus frontalis superior. Aging did not change the side asymmetry (laterality) of the gyri. In the central part of the auditory pathway above the inferior colliculus, a trend toward an effect of aging was present in the axial vector of the diffusion (L1) variable of DTI, with increased values observed in elderly subjects. A trend toward a decrease of L1 on the left side, which was more pronounced in the elderly groups, was observed. The effect of hearing loss was present in subjects with expressed presbycusis as a trend toward an increase of the radial vectors (L2L3) in the white matter under Heschl's gyrus. These results suggest that in addition to peripheral changes, changes in the central part of the auditory system in elderly subjects are also present; however, the extent of hearing loss does not play a significant role in the central changes.
Keywords: senioři; AP; Auditory Diseases, Central; elderly subjects with expressed presbycusis; visual cortex; HG; white matter under Heschl’s gyrus; Aging; MR morphometry; auditory cortex; auditory pathway above IC; WM_HG; presbyakuze; white matter; Auditory Cortex; gray matter; PT; mean diffusivity; Auditory Pathways; inferior colliculus; planum temporale; IC; auditory pathway; GFS; mužské pohlaví; Diffusion Tensor Imaging; diffusion tensor imaging; Adult; mladý dospělý; EP; V1; GM; Presbycusis; presbycusis; magnetická rezonanční tomografie; centrální poruchy sluchu; young subjects with physiologic hearing/young controls; Magnetic Resonance Imaging; stárnutí; Young Adult; MD; sluchová dráha; ženské pohlaví; ROI; Humans; zobrazování difuzních tenzorů; FA; Heschl’s gyrus; MP; fractional anisotropy; gyrus frontalis superior; Nerve Fibers, Myelinated; region of interest; SNHL; WM; YC; sensorineural hearing loss; dospělí; aging; AC; elderly subjects with mild presbycusis; Female; nervová vlákna myelinizovaná; Aged; DTI; lidé; Male; sluchové korové centrum